Correction: Design and development of photoanodes for water-splitting dye-sensitized photoelectrochemical cells. (19th December 2016) - Swierk, John R.; Mallouk, Thomas E.
Abstract : Correction for 'Design and development of photoanodes for water-splitting dye-sensitized photoelectrochemical cells' by John R. Swierk et al., Chem. Soc. Rev., 2013, 42, 2357–2387.